Economic systems of the Commonwealth - Hoover, Calvin B.; Karmel. P. H. (Durham, N.C. : Published for the Duke University Commonwealth-Studies Center [by] Duke University Press, 1962)
These studies are descriptive analyses of the economic systems of Australia, Canada, New Zealand, South Africa, the United Kingdom, Malaya, India, Pakistan, Ceylon, Ghana and the West Indies.
Includes bibliographical footnotes.
aia 09/05/2018
Loans
Keywords: Economic History